The scope of public organisations with productive functions: insights from the inefficiency of Italian local public transport - Giacomo Di Foggia; Ugo Arrigo (European Journal of Government and Economics (EJGE), 2015)
It is a well-known fact that reforms necessary to enhance competition and make the economy more attractive play a major role in the Government activity in Europe. Considering the Italian state of affairs, this paper focuses on the inefficiency of public producers in the light of certain market and legal impediments. This paper describes key barriers that undermine the healthy functioning of an important industrial and service sector of the Italian economy: specifically local public transport. This paper also sheds some light on this problem analysing the impact that a controversial regulation framework may have on an industry and suggests that the degree of liberalisation affects the return on investments.
Keywords: 330; State-owned enterprises; efficiency; Italy; local public transport; competition